ANTIGENOTOXIC ACTIVITY OF GRACILARIA SP. ON ERYTHROCYTES OF NILE TILAPIA EXPOSED BY METHOMYL-BASED PESTICIDE - R.A. Islamy,; V. Hasan,; Sze-Wan Poong,; Y. Kilawati,; A.P. Basir,; A.S. Kamarudin, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research investigates the biochemical profile, antioxidant properties, and antigenotoxic activity of red seaweed (Gracilaria sp.) extract on micronuclei formation in peripheral blood erythrocytes of tilapia (Oreochromis niloticus) exposed to a methomyl-based pesticide. Results revealed a diverse phytochemical profile in the red seaweed extract, with the presence of alkaloids, triterpenoids, steroids, tannins, coumarins, terpenoids, quinine, phytosteroids, flavonoids, and phlobtannins. GC-MS analysis identified compounds such as Heptadecane, Neophytadine, Hexadecanoic acid, Oleic acid, and Adipic acid in the sample. The antioxidant activity exhibited a concentration-dependent response, demonstrating increased strength with higher extract concentrations. Antigenotoxic analysis indicated a significant reduction in micronuclei frequency in peripheral erythrocytes of tilapia. In conclusion, the research underscores the potential of red seaweed extract as a valuable natural resource with antioxidant properties and a mitigating effect on genotoxicity induced by pesticide exposure in aquatic organisms.